KENDALA PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TAHUN 2023 DESA KARANG SENTOSA KABUPATEN BEKASI - Dahuri, Adin; Yani, Yani (Jurnal Ilmu Administrasi Publik, 2025)
The reseach presents a description of identifiying and analizing with a qualitative approach regarding the obstacles in collecting Land and Building Tax of Rural and Urban Area (herein after refers to as PBB-P2) periode of 2023 in Karang Sentosa Subdistrict in Bekasi Regency. Data of PBB-P2 achievements sourced from local tax authority and interview conducted with tax officer and some taxpayers. The research shows that achievement rate of PBB-P2 collection in 2023 reached 27% due to contribution of some obstacles such as income decrement due to Covid-19, unoptimal utilization of ceritain alternative places for PBB-P2 payment, and there are also a few landowners who do not reside at Karang Sentosa Subdistrict, and unproportionate number of tax officer compared to taxpayers. Some improvements should be takan to increase the PBB-P2 collection in order to reach its target for the following years. These improvement efforts including conduct ongoing advise for taxpayers to pay their PBB-P2 on time, provides mobile PBB service vehicle stationed at Karang Sentosa Subdistrict office, establishing an intensive collabiration with head of community and neighborhood, and maximalized the utilixation of reguler meeting   namely "Rapat Minggon" as a channel of communication among tax officer and taxpayers as well as presenting the development of PBB-P2 achievement progress.